2004
DOI: 10.1063/1.1751227
|View full text |Cite
|
Sign up to set email alerts
|

Electrical study of Ge-nanocrystal-based metal-oxide-semiconductor structures for p-type nonvolatile memory applications

Abstract: Nonvolatile memory structures using Ge nanocrystals embedded in SiO2 have been characterized by room and low temperature current–voltage and capacitance–voltage measurements. The Ge nanocrystals have been fabricated by low pressure chemical vapor deposition process which is shown to be well suited for a real control of the tunnel oxide thickness. The deposition conditions allow a separate control of nc-Ge density and size. Using capacitance–voltage characterizations on nonvolatile memory structures, we have me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 15 publications
3
63
3
Order By: Relevance
“…Ge has a smaller band-gap than Si which makes it compatible with currently used metal oxide semiconductor (MOS) technology and also improves its write/erase speed [5,6]. Promising non-volatile properties of Ge-NCs were reported by several groups [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Ge has a smaller band-gap than Si which makes it compatible with currently used metal oxide semiconductor (MOS) technology and also improves its write/erase speed [5,6]. Promising non-volatile properties of Ge-NCs were reported by several groups [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This produces two phenomena: a faster charging process in Ge islands and a larger potential barrier for carrier leakage to the substrate, resulting in a larger retention time [3][4][5][6][7]. Recent theoretical studies have demonstrated the better retention properties of Ge NC memories, compared with those based on Si NCs and an ideal size for Ge islands of ~15 nm [8].…”
mentioning
confidence: 99%
“…However, research results in several groups have demonstrated the superior properties of Ge-based nanocrystal memories over those based on Si. [4][5][6] The Ge nanocrystals offer improved nonvolatile charge retention time due to their smaller band gap. The smaller band gap provides both a higher confinement barrier for the retention mode and a smaller barrier for the program and erase modes.…”
mentioning
confidence: 99%